ANALISIS KOMPETENSI PEGAWAI KANTOR CAMAT TAMPAN KOTA PEKANBARU - Melly Hardiyanti; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In the era of the current,local govermment are required moro creative and innovative in the operation of the bureaucracy therefore the professionalism of the bureaucracy should be mediating agent, the public interest as well as the interests of the government. In Law No. 23 year 2016 About Local government,the Ice-shelf the Republic Of Indonesia of the year 2016. 58. Therrefore from the perspective of local government the form,aims to further the welfare of society and enhance the competitiveness of the area,then this is a challenge and an opportunity for the government.The study aims to know two things, the first to know the competence of employess in service public and the second to know the factors that affect the competence of employees in service public. The research was carried out in the city of Pekanbaru, wiith locations in the head office of Tampan,Pekanbaru city.The methods of analysis data used in this study is qualitative descriptive, which is to reveal the facts, circumstances,the phenomenon,variables, and the situation that occurred with the situation in the community. The data used is the primary and the secondary, primary, from respondents or informants and data has come from the object of research.The results of research and discussion of the writers do there are five dimensions that affect the competence of employees in serving the people in the Head Office of Tampan,namely 1. This knowledge,are in the category of pretty good, 2. This expertise, are in the category of good, 3. This cooperation,are in the category of good, 4. The dimensions of quality,are in the category of pretty good, 5. The Head offiece of Tampan are in the category good . Keywords: Analysis, Competense.